An Empirical Analysis of Overtime Greek Regional Development Strategies/Policies the Period 1976-2015: The Case of the Region of Thrace (International Journal of Scientific Research and Management (IJSRM), 2020)
Thrace had and has relatively favor conditions for substantial development, that is, good and adequate physical, environmental and cultural resources, but paradoxically remains the poorest Greek region. What missed was the smart, consistent and effective regional development policies, capable of counterbalancing the disadvantages. Some not well-designed policies, based on generous financial incentives after 1976, contributed very little to its growth because they were fragmentary without focus and cohesion. They supported a shallow growth, unable to create a good/stable and sustainable basis for cost, quality and functional competitive advantages. Our empirical research proves well- documented the insufficiency of regional policies followed the last 40 years, 1976-2015. In this context, we suggest some indicative new regional policies that will have to be based on both, in smart incentives, supporting smart/flexible specialization well-branded globally and in intelligent production systems capable of supporting effectively, either outsourcing production via long term cooperation, or domestic production for niche markets.